Evaluation of retro muscular mesh repair technique for treatment of ventral hernia - Alkhayat, Mohammad M.; Saleh, Hatem A.; Nassar, Mohammed Nazeeh Shaker; El-Balshy, Mohammed Abd-El-Galil (International Surgery Journal, 2018)
Ventral hernias commonly encountered in surgical practice account for 15-20% of all abdominal wall hernias. Results of tissue repair have been disappointing. The optimal approach for abdominal incisional hernias is still under discussion. The aim of the study was to evaluate the retro muscular mesh repair technique in the treatment of ventral hernia as one of the standard techniques for treatment of such cases. This prospective study on 50 consecutive patients was performed from July 2016 to July 2017. Patients were prepared to be operated by the retro muscular mesh repair technique. All patients were evaluated with respect to operative time and postoperative complications. Results were documented and statistically analysed. In this study on 50 patients, there were 30 female patients (60%) and 20 male patients (40%). The age of the studied patients ranged between 26 and 65 years with mean age of 49.8 years. The mean operative time was 88.5±15.3 min. The mean period of drainage was 2.3±1.3 days. Seroma was encountered in one case only 2%. No recurrence was reported in the studied patients during the period of follow-up (12months). On the basis of this study, we conclude that retro muscular (sublay) mesh repair is the ideal technique for incisional hernia repair.